La dinámica de las políticas públicas a través de los servicios y prácticas en salud (2002)
ABSTRACT: This article makes a reflection about the possibilities to consolidate the public politics in the perspective of the rights to health services and practices. The objective is to regain some elements which are refer rings to understand the professional logic and participation of health workers, in the design of the politics implemented today for the health reality of the country, the institutions and social practice. The methodology for this paper focuses in an analytical review by the authors and other researchers. It concluded that a public politic that recognizes health as a right, requires from the subject who gives care to the one who receives it, to make explicit the professional identity, the representation the social interaction and the creation of required spaces for formation and work conditions, according to health problems -illnesses- attention and the social and sanitary needs of the population.